The relationship of entrepreneurial competencies and business success of Malaysian SMEs: the mediating role of innovation and brand equity / Azmi Umar and Rohana Ngah - Umar, Azmi; Ngah, Rohana (Universiti Teknologi MARA Cawangan Selangor, 2016)
This conceptual paper is to study the relationship of entrepreneurial competencies on business success in the context of Malaysian SMEs. In the recent study, when the business environment is hostile and dynamic, the entrepreneurial competencies are identified as the most important factor in business success. Entrepreneurial competencies are also connected directly to business performance. Beside entrepreneurial competencies, the entrepreneurs should also be competent to create an innovation and brand equity for business growth. The innovation and brand equity contributed to competitive advantages that lead to business growth and success. This paper adopts the Resource Based Theory (RBT) which emphasize that entrepreneurial competencies, innovation, and brand equity are valuable and intangible resources that lead towards the success of business. There is a dearth of studies that have examined the influence of innovation and brand equity on the relationship of entrepreneurial competencies on the success of Malaysian SMEs business. Therefore the current study strives to investigate the mediating impact of innovation and brand equity on the relationship between entrepreneurial competencies and SMEs business success. This conceptual study will contribute to the existing body knowledge as well as to entrepreneurs of Malaysian’s SMEs.